$$\log n+\log \frac{n}{2}+\log\frac{n}{4}+\log\frac{n}{8}+\cdots+\log\frac{n}{n}=\Theta (\log^2n).$$

The sum of logarithms is the logarithm of the product $n\cdot\frac{n}{2}\cdot\frac{n}{4}\cdot\frac{n}{8}\cdots\frac{n}{n}$. This equals $n^{\log n}$ divided by what? If the product would just be $n^{\log n}$, then this would make perfect sende since $ \log(n^{\log n})=\log(n)\cdot\log(n)=\log^2 n$. But the divisor equals $\frac{1}{2}\cdot\frac{1}{4}\cdot\frac{1}{8}\cdot\frac{1}{16}\cdots\frac{1}{n}$ so I don't get it.

  • 2
    $\begingroup$ Try to write the summation in the form $\sum_{i=0}^{\log n} a_i$ for a suitable $a_i$ (which also depends on $n$). Then you will likely find a better way to deal with the logarithm. $\endgroup$ – Discrete lizard Jul 31 at 12:17

Assuming $n$ is a power of $2$, you have: $$ \sum_{i=0}^{\log n} \log \frac{n}{2^i} = \sum_{i=0}^{\log n} \left( \log n - i \right) = \sum_{i=0}^{\log n} i = \frac{(\log n)(\log n+1)}{2} = \Theta(\log^2 n). $$

| cite | improve this answer | |
  • 1
    $\begingroup$ Thanks a lot! Why is $\sum_{i=0}^{\log n} \left( \log n - i \right) = \sum_{i=0}^{\log n}i$? $\endgroup$ – timtam Jul 31 at 13:02
  • $\begingroup$ The addends of the first sums are the integers from $\log n$ to $0$, in descending order. The addends of the second sum are the same integers but in ascending order. $\endgroup$ – Steven Jul 31 at 13:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.